The Zimbabwe Museum for Human Science (ZMHS) and the preservation and communication of cultural heritage - Razao, Reason (Midlands State University, 2019)
Cultural heritage is important because it strongly influences our sense of identity, our loyalties, and our behaviour. Within living memory tribes, peoples and nations are supposed to feature distinctive attributes and characteristics concerning their history, culture, religion, evolution level etc. Memory institutions (archives, libraries, museums, schools, and historic sites) have a responsibility for preserving and interpreting the cultural record, so there are practical reasons to study cultural heritage. Attention to cultural heritage leads to wider awareness of the complexity and cultural bases of archives, libraries, and museums. Specialized terms are explained. A vast number of classic literature, human science investigations and topical studies try to explain and analyse the phenomenon of differences between nations and its impacts on politics, economy and intercultural relations. The following study examines the role of cultural artefacts in articulating the past. This research sought to investigate the relevance of preserving cultural heritage and to assess if the artefacts in the ZMHS express the lives of the people who lived before. The research also assessed the extent to which these cultural heritage artefacts cultivate identity within the society and at the same time promoting minority cultural groups within Zimbabwe.